Stimulator of InterferoN Genes (STING)-Associated Vasculopathy with Onset in Infancy Syndrome (SAVI) Associated with Disseminated Molluscum Contagiosum Under Baricitinib Treatment - Thilo Gambichler; Yusa Devrim; Laura Susok (Dermato, 2025)
Background/objectives: Stimulator of Interferon Genes (STING)-associated vasculopathy with onset in infancy (SAVI) is a rare autoinflammatory disorder caused by gain-of-function mutations in the TMEM173 gene. These mutations result in chronic activation of the STING pathway and excessive type I interferon production, leading to systemic inflammation, vascular abnormalities, interstitial lung disease, and skin ulcerations. Janus kinase (JAK) inhibitors, including baricitinib, have shown promise in mitigating systemic and organ-specific manifestations. However, these inhibitors broadly suppress immune pathways, potentially increasing vulnerability to infections. Case presentation: This case report describes a 21-year-old woman with SAVI (due to a heterozygous TMEM173 mutation) who developed disseminated molluscum contagiosum (MC) while receiving baricitinib therapy. Laboratory results revealed lymphopenia, low CD4/CD8 ratio, and impaired immune cell activity, suggesting compromised antiviral immunity. Discussion: Despite SAVI’s association with excessive type I interferon signaling, this chronic hyperactivation may cause immune dysregulation, exhausting T cells and natural killer cells vital for viral defense. Furthermore, baricitinib suppresses interferon signaling via the JAK-STAT pathway, reducing inflammatory damage in SAVI but also impairing antiviral responses. Moreover, MC viruses evade host immune defenses by antagonizing STING and TANK-binding kinase 1-mediated interferon activation, further contributing to infection risk. This report is the first to document MC in a SAVI patient and highlights the rare complication of disseminated MC due to impaired type I interferon signaling and immune suppression from baricitinib therapy. This case underscores the need for vigilance regarding viral infections in SAVI patients treated with JAK inhibitors.